Trend Comparison Of Bank Sustainable Financial Statements Based On Assessment Of Economic Aspects, Environmental Aspects, And Social Aspects - Sutikno, Sutikno; Oktaviano, Egy Tri; Faroji, Fajar (Jurnal Keuangan dan Perbankan (KEBAN), 2023)
The acceleration of unbalanced economic development has an impact on environmental damage and social inequality. This article aims to find out how the trend of comparing sustainable financial statements in banks is based on assessments from economic aspects, environmental aspects, and social aspects. This sustainable financial report is the first time it has been applied to financial service institutions that have been determined based on the regulatory policies of the Indonesian Financial Services Authority. descriptive quantitative is used as a method that helps researchers in conducting research with trend analysis of sustainable financial statements comparison in banking from 2020-2021, at the bank that won the Annual Report Award in the Category of Listed Financial Banking. Research results based shows that economic, social, and environmental damage can be overcome with awareness by each bank in providing financing to consumers who care about these three aspects. This sustainable financial report is so that it can be used by the company as a policy improvement on the awareness of the financial services industry to apply from economic, environmental, and social aspects